ASSESSMENT OF HEALTH CARE PROFESSIONALS KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS INFECTION CONTROL IN LABOUR ROOM (International Journal of Ayurveda and Pharma Research, 2016)
Women in labour rooms are exposed to invasive devices and procedures that can cause significant infection risk. Although the period of contact is generally short, but the infection risk associated with care in labour rooms is probably quite high. The purpose of the study was to assess health care workers knowledge, attitude and practice towards infection control in labour room at Chaudhary Braham Prakash Ayurvedic Charak Sansathan New Delhi. A Questionnaire was prepared to assess the knowledge, attitude and practice of health care workers towards infection control in labour room. After a month of data collection I have found that only 50.02% of the health care professionals were adhered to infection control measures in labour room. Out of that nursing staff have the highest degree of knowledge and practice of infection control precautions. The good infection control practice is acquired by experience over years of work.